Namudhaj / Mohd Azrul Amri Azri ... [et al.] - Azri, Mohd Azrul Amri; Samin, Mukhtar; Rashid, Nur Ain Syafiqah; Isnkandar, Siti Nabila; Mohd Rahim, Farrah Azrah (2016)
After doing some sort of research on the business opportunity available in Batu Pahat, we decide to specify our business in selling our services. Our business comes up with a business plan of partnership whereby our business name will know as "Namudhaj" In trying to establish this business plan, all aspects including the four major of business establish such as administration, marketing, operation, and financial are seriously taken into consideration. The administration part will tell about the administration objective, vision, mission, goals, and organization strategies. In addition, the responsibility of the admin is to determine the structure, chart, location, schedule of tasks and responsibilities, remuneration, and administrative budget. For the operation plan, we will explain about operation objective, operation strategy which includes short and long-term strategy, and product that our. premises provide. Besides that, the operation- plan also provide operation process, process flow. chart, business hour, material requirement, suppliers, and operation budget. The marketing and financial plan is carefully handled in order to obtain maximum profit using the best forecast. This is very important because the factor that determines the percentage of profit and allocation of the market share in selling product which eventually affects both of them. As we know our capital and estimate our expenses correctly, we will succeed in predicting our profit and loss in our product. We sincerely hope this a guideline which- given to us will drive successfully and correct our mistake. So that we can try to improve and, make-our-business accepted by all.